Analyzing Vietnam’s Economic Transformation from 2007 to 2023: Insights from Structural Decomposition of Input–Output Tables - Nguyen Thi Bich Ngoc; Ichihashi Masaru; Bui Xuan Hong (Economies)
The present study investigates Vietnam’s economic structural transformation from 2007 to 2023, identifying key sectors contributing to output growth and poverty reduction. The study is situated within the broader context of industrialization and sustainable development in emerging economies. It employs structural decomposition analysis using Vietnam’s national input–output tables for the years 2007, 2011, 2015, 2019, and 2023. The analysis decomposes changes in total output into technical effects and final demand effects, allowing for an evaluation of the relative contributions of sectoral productivity and demand side factors. The findings of the study indicate that the manufacturing and services sectors have been the primary drivers of economic growth, with the electrical and optical equipment, food, beverages and tobacco, and basic metals sectors demonstrating particularly strong performance. The factor of final demand, which is derived from consumption, investment, and exports, has played a dominant role in driving output. Notably, export-led manufacturing has experienced significant benefits due to Vietnam’s engagement in free trade agreements. It is noteworthy that the agriculture sector demonstrated a period of recovery between 2019 and 2023, driven by an increase in final demand. This study underscores the pivotal function of sectoral adaptability, trade openness, and strategic policy in maintaining inclusive economic development. It is evident that the phenomenon under scrutiny is not only indicative of vulnerabilities and opportunities but also shaped by global shocks, for example, the coronavirus pandemic.